Pengaruh Fundamental Perusahaan Dan Reaksi Pasar Modal Selama Terjadinya Pandemi Covid-19 Terhadap Return Saham (Studi Empiris 35 Perusahaan Market Kapital Terbesar Indeks Saham Syariah Indonesia Periode 2019–2022) - Alfiansyah, Muhadi; Prajanto, Agung (Badan Penerbit Universitas Muria Kudus, 2023)
This study aims to analyze the influence of company fundamentals and capital market reactions during the Covid-19 pandemic on the stock returns of companies with the largest market capitalization included in the Indonesia Sharia stock index for the 2019-2022 period. This study is quantitative research with a purposive sampling technique and a total sample of 35 companies that meet the criteria. This study uses secondary data, namely data from financial reports for the period 2019 to 2022 obtained from the official website of the Indonesia Stock Exchange. The test results using multiple linear regression analysis show that return on equity has a significant effect on stock returns, price to book value has a significant effect on stock returns, earnings per share has no significant effect on stock returns, and there is no significant difference from the abnormal return before and after the announcement of covid-19. This study aims to analyze the influence of company fundamentals and capital market reactions during the Covid-19 pandemic on the stock returns of companies with the largest market capitalization included in the Indonesia Sharia stock index for the 2019-2022 period. This study is quantitative research with a purposive sampling technique and a total sample of 35 companies that meet the criteria. This study uses secondary data, namely data from financial reports for the period 2019 to 2022 obtained from the official website of the Indonesia Stock Exchange. The test results using multiple linear regression analysis show that return on equity has a significant effect on stock returns, price to book value has a significant effect on stock returns, earnings per share has no significant effect on stock returns, and there is no significant difference from the abnormal return before and after the announcement of covid-19.